Development of an automated GIS tool for reproducing the HAND terrain model. (April 2018) - Rahmati, Omid; Kornejady, Aiding; Samadi, Mahmood; Nobre, Antonio Donato; Melesse, Assefa M.
Abstract: Height Above the Nearest Drainage (HAND), a state-of-the-art topo-hydrological index, has been increasingly used in geo-environmental studies. It describes the local normalized drainage potential of a large region. To date, a trial and error and cumbersome multistep process has been used to obtain the HAND index which does not result in an optimal threshold for contributing area. This study aims at developing a user-friendly geographic information system (GIS) tool, HANDTool, using the Python programming language. We successfully applied the tool for the Chehel-Chai watershed, Iran and the random forest algorithm was used to model groundwater potential. Results revealed that the HAND index made a great contribution to groundwater potential modeling among the other conditioning factors. This tool gives valuable insights on the soil-topography-moisture shared interactions and vegetation condition, especially in ungauged watersheds. Highlights: HANDTool is a python tool for constructing a topo-hydrological map namely HAND. HANDTool was successfully applied for the Chehel-Chai watershed, Iran. A Random Forest algorithm was developed for groundwater potential modeling. The HAND index made a great contribution to groundwater potential modeling.